Factors Affecting the ICI during Indonesia's Economic Recession During the Covid-19 Pandemic : Faktor- Faktor yang Mempengaruhi IHSG pada saat Resesi Perekonomian Indonesia Selama Pandemi Covid-19 - Amilia Ristika Dewi; Heri Widodo (Academia Open, 2021)
The study used in this study aims to determine the factors that can affect the JCI, namely the rupiah exchange rate, inflation, and interest rates during the Indonesian economic recession during the Covid-19 pandemic. The research method used in this study uses quantitative and The secondary data used is secondary data from the BEI and BI which was collected from 6 Nov 2020 to 3 Feb 2021 with a data collection technique, namely the documentation method. Saturated sampling is used in the sampling technique. So that obtained as many as 59 samples. While the techniques used in data analysis in this study are classical assumption test and multiple linear regression analysis as hypothesis testing. JCI. However, inflation in a partial test does not have a significant effect on the JCI.